Electoral authoritarianism and weak states in Africa: The role of parties versus presidents in Tanzania and Cameroon. Issue 1 (January 2018) - Morse, Yonatan L
State capacity is arguably an essential factor that stabilizes electoral authoritarian rule. Yet, in the context of sub-Saharan Africa many measures of state capacity are generally weak. What therefore explains the persistence of electoral authoritarianism in Africa? This study provides a comparison of Tanzania and Cameroon to highlight two divergent reactions to the problem of power consolidation in Africa. In Cameroon, a centralized presidency and comparatively large coercive apparatus underpinned a strong patrimonial state. By contrast, in Tanzania the ruling party became an institution that integrated elites and appeared to subsume the state. These regime configurations stabilized electoral authoritarianism in unique ways, and led to different dependence on the state during elections. The study sheds new light on contemporary Africa, and the diverse sources of authoritarian resilience in the face of multiparty elections.